Sustainable Tourism and Housing Development for Panggang Island, Seribu Islands Jakarta: Learning from Maldives' Sustainable Tourism Development - Gunawan Tanuwidjaja; Mustakim (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2022)
In 2016, Indonesia's tourism sector contributed 4 per cent of the Indonesian Gross Domestic Product (GDP). By 2019, the Indonesian Government wants to increase the tourism contribution to 8 per cent of GDP, requiring 20 million tourist visits. Ten